Design of Protection Strategies and Performance Analysis of an HVDC Link During Multiple Disturbances - Hameurlaine, A.; Sayah, H.; Boukezzi, L. (Engineering, Technology & Applied Science Research, 2022)
In High Voltage Direct Current (HVDC) transmission system applications, the control and protection system plays an essential role in the overall performance. This paper aims to give solutions to some performance problems that can occur in the HVDC link. In this paper, ways to mitigate this serious malfunction of the commutation failure process in the operation of HVDC converters are studied and protection functions like the Commutation Failure Prevention (CFPREV) have been used. Furthermore, HVDC transmission systems are vulnerable to DC faults and its protection becomes ever more important with the fast growth in the number of installations. In this context, the DC fault protection function is one of the most important challenges to the development of HVDC transmission systems. The dynamics of the studied power system including the HVDC link are thoroughly investigated in this paper through various simulation scenarios.